Rückläufige Verkehrsmengen?! Welche Konsequenzen zieht die Regionalplanung für ihr funktionales Straßennetz? Das Beispiel Mittelthüringen - Liebe, Lars; Weiß, Ute (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
This article considers the extent to which it is now necessary to make adjustments to socalled “functional road networks”, an instrument of comprehensive spatial planning, in response to changes in demographics. Drawing on a case-study of the Central Thuringia planning region, the analysis focuses initially on the question of whether population shrinkage and ageing actually impact on levels of road traffic, or whether their effects are offset by other factors. As the authors report, road-traffic volumes are no longer growing relentlessly; in the period between 1995 and 2000, they were, in some areas, already in decline. Additional growth in the future is likely, however, essentially on those routes which are of European significance, whilst the more sparsely populated rural regions are expected to see a continuing decline in traffic levels. The conclusion drawn by the authors in the light of prevailing demographic and financial circumstances is that regional planning can — and should — no longer go on calling for the expansion of all categories of the functional road network on a large scale (as has previously happened in Central Thuringia); it should rather address the issues thrown up by the actual development of traffic volumes.